Excessive use of computer: computer games addiction / Intan Liyana Zulkifli - Zulkifli, Intan Liyana (2007)
The objectives of this research are to find out the existence of computer games addiction among FITQS students and to identify the effects of the addiction. This research is done by conducting a survey, distributing questionnaire precisely, within the faculty to collect data from students to be processed by using a statistical tool. After conducting an analysis, the result turns to be that 74% of the targeted audience is addicted to computer games. It is found that this problem can affect gamers in several ways such as health conditions, communication with society and surrounding, study performance, and financial state. It is recommended that this research is continued so that more information on this area can be gathered for future references and is adaptable to our country's environment.